2013
DOI: 10.3109/03639045.2013.788011
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil vaginal suppositories: preparation, characterization,in vitroandin vivoevaluation

Abstract: This study demonstrated enhanced sildenafil exposure in the uterus following IVG administration of SVS, which could be used to target the uterus for therapeutic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The female rats were divided into four groups of 10 rats each. The first group was used as a control while other groups received SIL with a dose of 16.6 mg/kg of body weight of rats either oral solution through oral gavage, intravaginal CIS, or intravaginal FIS for 14 days (Shanmugam et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The female rats were divided into four groups of 10 rats each. The first group was used as a control while other groups received SIL with a dose of 16.6 mg/kg of body weight of rats either oral solution through oral gavage, intravaginal CIS, or intravaginal FIS for 14 days (Shanmugam et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty female mature Wistar rats weighing 200-250 g obtained from the experimental animal care center, Faculty of Veterinary Medicine, Beni-Suef University, were divided into three groups each comprising 10 rats. SIL was administered in a dose of 16.6 mg/kg (Shanmugam et al., 2014 ). Group 1 received oral SIL solution (2.25 mg/ml) in purified water, group 2 received the optimized intravaginal CIS and group 3 received intravaginal FIS.…”
Section: Methodsmentioning
confidence: 99%
“…It was noticed that the suppositories prepared using the glycerol-gelatin base shows almost the same hardness, weight variation and disintegration time than the suppositories prepared using the Witepsol, grade H15. 14 The drug release obtained from the prepared FLZ vaginal suppositories is shown in Figure 2. It was observed that the glycero-gelatin suppositories (FVS 3) released full amount of drug within 60.0 min of dissolution.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The final solution was filtered through membrane filter (pore size 0.45 µ) and the presence of drug was determined using UV visible spectrophotometer after suitable dilutions with acetate buffer at 261 nm wavelength. 8,28 Three suppositories were taken from each batch for this study.…”
Section: Content Uniformitymentioning
confidence: 99%
See 1 more Smart Citation